Pengaruh Kualitas Produk, Harga Dan Citra MerekTerhadap Keputusan Pembelian Produk Yamaha(Studi Kasus Pada Fakultas Ekonomi Ums) - Yuniyanto, Syofza Eko (2016)
The purpose of this research is 1) To know the influence of product quality of the decision the purchase of products Yamaha 2) To know the influence of the price of the decision the purchase of products Yamaha 3) To know the influence of image brand of the decision the purchase of products Yamaha 4) To know the influence of quality products, prices and image brand of the decision the purchase of products Yamaha. Population in this study student muhammadiyah university school of economics surakarta and those used in research has reached 41.82 respondents rounded to 42 the treatment respondent. The researchers used samples from 42 respondents this is because the greater the total sample approaching population, then opportunities generalization the less mistake. Based on the results of the analysis t test known that the quality of the product (X1) have an significant of the decision a purchase with supported value t.sig (0,001) smaller than 0.05 (α). Prices (X2) have significant influence of the decision to buy (Y) and supported value t.sig (0,001) smaller than 0.05 (α). With brand image (X3) have an significant of the decision a purchase with supported value t.sig (0,015) smaller than 0.05 (α). The results of the analysis F test obtained Fcount > Ftable (11,793 > 3,23), then Ho rejected. Means jointly variable quality products (X1), price (X2) and brand image (X3) significant of the decision of the purchase (Y). so that the model used in this research can be said to be fit. The results of the analysis the coefficients determined (R2) obtained adjusted R Square (R2) square as much as (0,441), means variation of change of the variables decision the purchase can be explained by variable quality products (X1), price (X2) and brand image (X3) for 44,1%. While the rest of 55,9 % described by other variables out model. While the result of data analysis known variable quality products , prices and brand image significant both individually and together with the resolution of the purchase , thus research is equal to research has been tested kurniawan ( 2006 ) and joko sulistiyono ( 2005 ) because all independent variable the product quality , prices and brand influential image of the decision purchase.